IoT-Based Water Quality Monitoring System Using ESP32 with NSF-WQI Method on Various Water Sources - Ulfa Niswatul Khasanah; Moh. Mimbar Fauzi; Fatra Nonggala Putra; Imroatul Fatikha Kurniati; Januar Gilang Ramadhan (Jurnal Teknologi Informatika dan Komputer, 2026)
Water quality is an important indicator in maintaining environmental health and ecosystem sustainability. Direct water quality monitoring would be challenging for determining the quality of water sources. Therefore, it is necessary to design a real-time Water Quality Index (WQI) monitoring system based on the Internet of Things (IoT) using the ESP32 microcontroller with sensors for pH, temperature, turbidity (NTU), Total Dissolved Solids (TDS), and electrical conductivity (EC). The system is designed to be portable with a battery power source and is capable of sending data in real-time to a server for display via a web interface, as well as providing automatic notifications through Telegram.Water quality assessment is performed using the National Sanitation Foundation Water Quality Index (NSF-WQI) method with four main parameters: pH, temperature, NTU, and TDS. The system is also capable of classifying water quality into 5 categories: Excellent, Good, Medium, Bad, and Very Bad. Laboratory tests were conducted on various liquids (coffee, soap, and milk), followed by field tests at three locations: Tempur River, Paddy Field Irrigation Flow, and Mbelik Tirta Wening Minggirsari Water Source. The measurement results show WQI values of 65–69 (Medium category) for Tempur River, 75–83 (Good category) for Paddy Field Irrigation Flow, and 93–98 (Excellent category) for Mbelik Tirta Wening Minggirsari Water Source. The system successfully demonstrated accurate, responsive, and reliable performance, making it suitable for sustainable water quality monitoring.